Microstructure, wear and corrosion characteristics of Cu matrix reinforced SiC–graphite hybrid composites. (August 2019) - Jamwal, Anbesh; Prakash, Prem; Kumar, Devendra; Singh, Neera; Sadasivuni, Kishor K; Harshit, Kumar; Gupta, Sumit; Gupta, Pallav
The aim of the present study is to investigate the effect of SiC-graphite reinforcement on the properties of pure copper. Copper matrix composites with SiC-graphite reinforcement (0, 2.5, 5, 7.5 and 10 wt.%) were prepared by stir casting process. Microstructure, phase, density, hardness and wear rate of prepared samples have been investigated. X-ray diffraction revealed that there is no intermediate phase formation between the reinforcement and matrix as a result of interfacial bonding between them. Microstructure study shows the uniform distribution of SiC-graphite particles in the Cu-matrix. Mechanical and corrosion properties of these Cu matrix MMCs were found to be dependent on the reinforcement content. Hardness was found to decrease with the addition of graphite due to its soft nature. Composite containing 5 wt.% reinforcement has shown minimum wear rate and maximum corrosion resistance. It is expected that the present composite will be useful for thermal management applications especially in heat exchangers.